Application of oxidation processes in wastewater quaternary treatment for organic compounds, antibiotics and nonsteroidal anti-inflammatory drugs removal and disinfection - Małgorzata Komorowska-Kaufman; Joanna Zembrzuska (Desalination and Water Treatment)
Reducing the content of micropollutants, including pharmacological ones, in treated wastewater discharged to the receiver, as a result of the introduction of legislative changes, is currently an urgent matter. The commonly used biological wastewater treatment system does not remove it effectively, and expansion with a quaternary wastewater treatment step will be necessary. In the presented research, wastewater treated at a municipal wastewater treatment plant (WWTP) with the removal of biogenic compounds was subjected to further purification processes using hydrogen peroxide, Fenton’s reagent, UV254 irradiation and a combination of these methods, and, for comparison, coagulation with the use of FeSO4. The effectiveness of the methods was determined in terms of removing organic compounds, including non-steroidal anti-inflammatory drugs (fenoprofen, ketoprofen, paracetamol, naproxen, ibuprofen, diclofenac) and antibiotics (trimethoprim, sulfamethoxazole) and reducing the number of psychrophilic and mesophilic bacteria. The best effects of the removal of organic compounds (TOC) were achieved by the Fenton (43.9 %), Fenton+UV254 (51.4 %) and H2O2 (43.5 %), with final carbon concentrations of 7.9–9.1 mg C/L. The process configurations showed different effectiveness in removing pharmaceutical substances. The Fenton process or irradiation combined with H2O2 achieved the removal of all tested pharmaceuticals above 96 %, except for fenoprofen (in the range of 74–83 %) and ibuprofen (90–93 %). The use of UV254 irradiation had the best disinfection effectiveness. For an exposure time of 60 min, with and without H2O2, a higher than 99.99 % reduction in bacteria was achieved.